A Comparative Validation Study of Fluconazole by HPLC and UPLC with Forced Degradation Study. (4th December 2013) - Jebaliya, Hetal; Patel, Madhavi; Jadeja, Yashwant; Dabhi, Batuk; Shah, Anamik
Abstract : The simplest stability indicating reversed phase Isocratic HPLC and UPLC methods has been developed and validated for the determination of fluconazole in bulk and solid pharmaceutical dosage form. A SunFire C18 (250 × 4.5 mm, 5  μ m particle size) column has been used for HPLC and BEH C18 (100 × 2.1 mm, 1.7  μ m particle size) column used for UPLC. The Mobile phase consisted of Methanol : Water (70 : 30) for HPLC and Methanol : Water (55 : 45 v/v) for UPLC. Isocratic flow was set at 1 mL/min and 0.30 mL/min, respectively, for HPLC and UPLC. For both HPLC and UPLC system detection has been performed at 211 nm with 30°C column oven temperature (good elution was obtained at 30°C) and injection volume, respectively, 2  μ L and 20  μ L for HPLC and UPLC.